2019
DOI: 10.3989/mc.2019.06618
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-activated binary concrete based on a natural pozzolan: physical, mechanical and microstructural characterization

Abstract: This article presents the physical, mechanical and microstructural characterization of an alkali-activated binary concrete (AABC) based on a natural pozzolan (NP) of volcanic origin (70%) and granulated blast furnace slag (GBFS) (30%) cured at room temperature (25°C). A solution based on the combination of NaOH and waterglass (Na2SiO3·5H2O) was employed as an alkaline activator. The concrete design was obtained using a modified version of the “absolute volume” method (ACI 211.1). The performance of the AABC wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…Taking into account the results of isothermal calorimetry, setting time and compressive strength, the hybrid cement could be classified, according to ASTM C1157 and NTC 121, as a low heat of hydration cement (LH type) as can be corroborated in Table 5. In accordance with the results reported by Robayo et al [24] and Valencia-Saavedra et al [19], using other precursors, the hybrid concrete showed a high level of workability, associated with a high fluidity (24 cm settlement) (Figure 10a), without the presence of segregation phenomena (Figure 10b) due to the adequate cohesiveness of the mixture, mainly promoted by the presence of sodium silicate. Additionally, the modulus of rupture (MR) of the material was determined by means of the flexural strength test.…”
Section: Reaction Kinetics Of the Hybrid Cementsupporting
confidence: 90%
See 1 more Smart Citation
“…Taking into account the results of isothermal calorimetry, setting time and compressive strength, the hybrid cement could be classified, according to ASTM C1157 and NTC 121, as a low heat of hydration cement (LH type) as can be corroborated in Table 5. In accordance with the results reported by Robayo et al [24] and Valencia-Saavedra et al [19], using other precursors, the hybrid concrete showed a high level of workability, associated with a high fluidity (24 cm settlement) (Figure 10a), without the presence of segregation phenomena (Figure 10b) due to the adequate cohesiveness of the mixture, mainly promoted by the presence of sodium silicate. Additionally, the modulus of rupture (MR) of the material was determined by means of the flexural strength test.…”
Section: Reaction Kinetics Of the Hybrid Cementsupporting
confidence: 90%
“…Additionally, the presence of unreacted FA particles is observed, corresponding to the crystalline phases of the FA, well adhered to the matrix through a homogeneous interface. These unreacted particles fulfill the function of a micro-aggregate, favoring the mechanical behavior of the compound (hybrid concrete) [24]. Finally, an optimal interface that ensures mechanical cohesion between the matrix phase and the aggregates (fine and coarse) was observed, very much in keeping with the good behavior obtained.…”
Section: Microstructural Analysis Of Hybrid Concretementioning
confidence: 54%
“…Table 4 lists the physical and morphological properties of the siliceous, limestone, and recycled aggregates used. The humidity, water absorption, and density values of S, L, and R aggregates were determined according to EN 1097-6-2014 [30], while the bulk density and percentage of voids were determined according to the EN 1097-3 standard [31] for the different particle size fractions of aggregate S, and for same grain size (as S D max 2 mm) for aggregates L and R. Morphological characterization (including the aspect, circularity, and convexity values) was determined according to the methodology proposed by Westerholm and Hafid [32,33] and Equations (1) to (3).…”
Section: Methodsmentioning
confidence: 99%
“…In other words, the AAM mortars required more liquid to attain the same spread as OPC. That may be attributable to the greater density of the waterglass and 10M NaOH activators (around 1.27 g/cm 3 ). An earlier paper [15] reported the need for a higher liquid/solid ratio in AAFA-10M mortars and the generally greater AAM mortar sensitivity to change in liquid/solid ratios.…”
Section: Mortar Liquid/solid Ratio Required For Plastic Consistencymentioning
confidence: 99%
See 1 more Smart Citation